The Effect of Short Story on Student’s Reading Comprehension at The Eight Grade Students of Mts. Abdi Bina Insani Jiput Pandeglang - Hayati, Nida; Riandi, Riandi; Novari, Ari Fajria (Universitas Mathla'ul Anwar Banten, 2024)
This research aims to determine the effect of using short stories on students' reading comprehension. Reading comprehension is one of the essential skills in learning English which is often a challenge for students. In this research, short stories were chosen as a learning medium to increase students' interest and motivation in reading, and make it easier for them to understand the text. Students find it difficult to understand English lessons because they have not mastered basic reading skills, both in English and their mother tongue. This research uses an experimental method with a pre-test and post-test design. Data were analyzed using the t test to determine significant differences between the two groups. The results of the research show that there is a significant increase in the reading comprehension of students who learn using short stories compared to students who use the comic method. This shows that the use of short stories as open-ended material can improve students' reading comprehension skills effectively. Data was collected through pre-test and post-test, then analyzed using normality T-test, homogeneity test, and paired t-test with the help of SPSS 22. The effect of Shrot Story on students of reading comprehension at the eight grade student of MTs. Abdi bina insani jiput Pandeglang in Academic Year 2023/2024 is. This is proven by the t-test value in the paired t-test of -11.158 with a df of 19 and a two-sided significance of 0.000, which means Ha is accepted and Ho is rejected. In other words, there is a significant difference in post-test scores between the experimental and control classes. It can be concluded that the use of short story strategies significantly improves The reading ability of students at Mts Abdi can be human strategies provide a better understanding of the structure and techniques of short story books and more overall ideas, and improve their reading abilities